Risk Factors for Seborrhoeic Dermatitis Flares: Case-control and Case-crossover Study - Rémi Lancar; Pascale Missy; Alain Dupuy; Philippe Beaulieu; Laurence Fardet; Dominique Costagliola; Olivier Chosidow (Medical Journals Sweden, 2020)
Patients with flares of seborrhoeic dermatitis were compared with control outpatients seen during the same time-period in a case-control study, and with themselves while in remission in a case-crossover study. All patients consulted the same office-based dermatologist. During the study period, 189 cases and 189 controls were included in the case-control study, and 81 cases in the case-crossover study. Multivariate analysis was performed. Case-control study results were the following: past history of tobacco consumption (odds ratio (OR) 2.2 (95% confidence interval (CI) 1.1-4.6)), conflict as a dispute during the past month (OR 10.6 (95% CI 1.0-114.3)), alcohol consumption on a regular basis (OR 10.2 (95% CI 2.0-52.6)), and higher level of stress during the past month (OR 8.2 (95% CI 3.4-19.9)). Case-crossover study results were the following: higher level of stress during the past month (OR 4.5 (1.7-12.2)), association borderline significant for higher level of alcohol consumption (OR 5.4 (0.8-34.9)). These risk factors for flares of seborrhoeic dermatitis should be taken into account carefully in the daily management of seborrhoeic dermatitis.